Stability of Styrax benzoin extract and fraction with the addition of glycerol and tween 80 - Dedi P Simatupang; Nora Susanti; Jamalum Purba (Pascasarjana Universitas Negeri Medan, 2021)
This research to decide the consequences of expanding the steadiness of the concentrate and part of incense with the expansion of glycerol and tween 80 by contrasting the reference tests of frankincense separates available. The technique utilized in this examination depends on the expansion of glycerol and tween 80, just as directing boundaries of consistency, organoleptic, pH and investigation of substance content of concentrates and parts with GC-MS instruments. The outcomes got in this investigation demonstrate the actual properties of the concentrate and part of the incense sap as a thick fluid, earthy red and has an unmistakable fragrant smell. The consistency got from the thickness test was 277.68 Cp. In the meantime, the thickness estimation consequences of the reference test acquired a consistency worth of 326.54 cP. What's more, has a pH scope of 4.0-5.5. The fundamental synthetic parts of the extraction results and the isoprophyl part of styrax benzoin and the reference part of the reference styrax benzoin remove dependent on the consequences of the investigation discovered 6 mixtures that share practically speaking, in particular Benzoic corrosive, Vanillin, trans-Cinnamic corrosive, (Z) - Cinnamyl benzoate, 2-Propenoic corrosive , 3-phenyl-, phenylmethyl ester, (E) - and Cinnamyl cinnamate. Keywords: Styrax benzoin, Glycerol, Extract stability, Tween 80, Fractionation